Harvard University Art Museums Bulletin. (Cambridge-Massachusetts : Harvard University Art Museums, 1992)
The Harvard University Art Museums Bulletin began in 1992. Included were articles about activities, exhibitions, acquisitions, programs, finances, and staff. Some issues were devoted to one or two exhibitions and included research, checklists, and bibliographies. It was published 2-3 times a year through the spring of 2000. (Jstor)
Online: https://www.jstor.org/journal/harvunivartmuse
Engels
Tijdschriften
Keywords: Harvard University Art Museums (Cambridge-Massachusetts).